A Simple Strategy to prune Neural Networks with an Application to Economic Time Series - Johan F. Kaashoek; Herman K. van Dijk (Tinbergen Institute, 1997)
A major problem in applying neural networks is specifying the sizeof the network. Even for moderately sized networks the number ofparameters may become large compared to the number of data. In thispaper network performance is examined while reducing the size of thenetwork through the use of multiple correlation coefficients andgraphical analysis of network output per hidden layer cell andinput layer cell.
Keywords: 330; Neuronale Netze; Zeitreihenanalyse; Theorie